Revisiting the relationship between leverage and firm value: does managerial ownership matter? - Hermeindito Hermeindito; I Wayan Nuka Lantara (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study aims to revisit the role of managerial ownership (MOWN) on the relationship between leverage and firm value. This study develops a non-monotonic model to test the managerial entrenchment hypothesis regarding the substitution of leverage and managerial ownership, and its impact on firm value. This study uses a sample of 108 manufacturing firms listed on the Indonesia Stock Exchange from 2014 to 2018, with a total of 540 firm-years. Using a weighted two-stage least squares, this study finds that the relationship between leverage and firm value is inverted N-shaped in firms without MOWN, and convex asymmetry in firms with MOWN. The first negative slope is greater than the subsequent negative slopes in firms without MOWN, indicating that underinvestment and managerial entrenchment issues are more sensitive than the trade-off between debt tax shield and default risk. Conversely, firms with MOWN are more directed towards the issue of trade-off theory. Firms with MOWN have lower performance than firms without MOWN, which implies that there is a critical problem in the selection of executives based on ownership structure, rather than on professional competence and skills.